0661 Lightbox Therapy for Seasonal Affective Disorder in College Students. (25th May 2022) - Zhang, Meina; Guist, Caitlin; Rossmann, Patrick; Moon, Chooza
Abstract: Introduction: Seasonal affective disorder (SAD) is a mental health issue that can be defined as depressive mood disturbances that align with a seasonal pattern. Research shows that college students are at a higher risk of having SAD leading to poor academic performance and other severe mental disorders. Light therapy can help alleviate the symptoms of SAD. However, few detailed investigations have been conducted on the impacts of light therapy for SAD symptoms and adherence barrier for the therapy. The purpose of this project was to review a light therapy program for college students. Specifically, we aimed to assess the changes in depressive symptoms before and after using a light box and assessed feedback. Methods: 207 college students (mean age of 22.5 years (SD=5.3); female (80.7%)) participated in the light therapy program. Participants were given user instructions and asked to utilize the lightbox daily. Participants completed the patient health questionnaire (PHQ-9) at baseline and when they returned the lightbox along with their feedback of this therapy. Students also completed the open-ended questions. We used paired sample t-test to assess changes in the total PHQ-9 score. Results: Participants spent 45 days, on average, using the device. Results showed that there was a significant decrease in PHQ-9 score from pre- to post-therapy [M(post-pre) = -2.78; p < .0001]. Most students said the therapy was effective (96.5%) and helped ease SAD symptoms and improve their mood. Some students planned to purchase a light box after the therapy. The major adherence barriers were finding enough time to use it and excessive brightness issue. Conclusion: The findings suggest that light therapy has positive outcomes in easing college students' SAD symptoms. Future randomized control trials are needed to assess the effectiveness of the intervention. However, to the time and brightness issues need to be assessed when designing the therapy instructions for college students. Support (If Any): This work was supported by the Alzheimer's Association Research Grant (AARG-19-618403), University of Iowa Institute for Clinical and Translational Science (NIH/NCATS, UL1 TR002537), and the University of Iowa Center for Advancing Multimorbidity Science (NIH/ NINR P20 NR018081).